2019
DOI: 10.3390/data4040145
|View full text |Cite
|
Sign up to set email alerts
|

Tree Cover for the Year 2010 of the Metropolitan Region of São Paulo, Brazil

Abstract: Mapping urban trees with images at a very high spatial resolution (≤1 m) is a particularly relevant recent challenge due to the need to assess the ecosystem services they provide. However, due to the effort needed to produce these maps from tree censuses or with remote sensing data, few cities in the world have a complete tree cover map. Here, we present the tree cover data at 1-m spatial resolution of the Metropolitan Region of São Paulo, Brazil, the fourth largest urban agglomeration in the world. This datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Datasets made for buildings or vegetation segmentation are useful but not entirely sufficient in our case. Those datasets include the Massachusetts Buildings Dataset [26], the Inria Aerial Image Labeling Dataset [25], the AIRS Automatic Mapping of Buildings Dataset [8], the Agriculture-Vision a Large Aerial Image Database for Agricultural Pattern Analysis [9] and the Tree Cover dataset for the year 2010 of the Metropolitan Region of So Paulo [33].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Datasets made for buildings or vegetation segmentation are useful but not entirely sufficient in our case. Those datasets include the Massachusetts Buildings Dataset [26], the Inria Aerial Image Labeling Dataset [25], the AIRS Automatic Mapping of Buildings Dataset [8], the Agriculture-Vision a Large Aerial Image Database for Agricultural Pattern Analysis [9] and the Tree Cover dataset for the year 2010 of the Metropolitan Region of So Paulo [33].…”
Section: Related Workmentioning
confidence: 99%
“…Table 1 presents the comparison of the statistics between the proposed dataset and closely related aerial datasets: Inria [25], AIRS [8], Massachusetts [26], Agriculture-Vision [9] and Tree Cover [33]. The older ones have a worse resolution (Tree Cover, Massachusetts).…”
Section: Comparison To Related Datasetsmentioning
confidence: 99%
“…Martins et al applied FCN, U-NET, Seg-Net, DeepLabV3+ and a dynamic dilated convolution network to the Campo Grande area for urban tree canopy mapping and obtained IOU ranging from 70.01% to 73.89% [27]. Wanger et al applied the U-NET model to São Paulo, Brazil, and obtained an overall accuracy of approximately 96% [57]. Existing studies have shown that U-NET is the fully convolutional neural network that currently performs the best for urban tree canopy mapping tasks after comprehensively considering indicators such as accuracy and the number of model parameters [27,58].…”
Section: Introductionmentioning
confidence: 99%